Intellectual Influences between the West and the Muslim World – Religious Authority in Transnational Interaction - Karman, Karen-Lise Johansen (Women, Gender & Research, 2007)
Is the scholarly interrelatedness between Muslim scholars in Western Europe and in the Middle East a one-way mode of communication from the traditional loci for Islamic authority to the West? Or does a multidirectional exchange of ideas exist? These questions are addressed by examination of legal opinions on gender issues.